Pengaruh Investor Attention dan Economic Policy Uncertainty Terhadap Kinerja Pasar Saham Bank KBMI 4 - Muhammad Yoga Pratama; Gatot Nazir Ahmad; Ryna Parlyna (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This research is motivated by the phenomenon of increasing retail investor participation in the digital era and rising global economic uncertainty affecting capital market dynamics. This study aims to analyze the influence of behavioral finance aspects proxied by investor attention and global macroeconomic aspects proxied by US Economic Policy Uncertainty (US EPU) on stock market performance, specifically stock return and stock liquidity. The unit of analysis in this study is the banking companies under the Core Capital Bank Group (KBMI) 4 category listed on the Indonesia Stock Exchange (IDX), selected due to their largest market capitalization and high liquidity. This study employs a quantitative approach using daily secondary data. The data analysis technique used is panel data regression with the Fixed Effect Model (FEM) estimation, corrected using Robust Standard Error (White) to address heteroscedasticity issues. Hypothesis testing was conducted to observe the partial and simultaneous effects of independent variables on dependent variables. The results reveal diverse empirical findings. First, investor attention proxied by Google Search Volume Index (GSVI) has a negative and significant effect on stock return, indicating that a surge in information search is interpreted by the market as a risk signal due to information asymmetry, thereby triggering selling pressure. Second, investor attention has a positive and significant effect on stock liquidity, proving that information dissemination can encourage market participation. Third, US EPU does not have a significant effect on stock return, demonstrating the high resilience of Indonesia's banking fundamentals against global issues. Fourth, US EPU has a negative and significant effect on stock liquidity due to investors' wait-and-see behavior. This study recommends that investors be more rational in filtering digital information to avoid momentary panic, and suggests that regulators monitor digital sentiment as an early indicator of market volatility.